THU0402 Efficacy and safety of canakinumab in patients with NOMID/CINCA. (23rd January 2014) - Goldbach-Mansky, R.; Sibley, C.; Felix, S.D.; Brewer, C.; King, K.; Zalewski, C.; Kim, H.J.; Bishop, R.; Chakraborty, A.; Colin, L.; Chioato, A.
Abstract : Background: Neonatal onset multisystem inflammatory disease (NOMID) is the most severe subset of patients (pts) with cryopyrin associated periodic syndromes (CAPS). IL-1 inhibitors are the mainstay of therapy for CAPS, however, the efficacy of longer acting IL-1 inhibitors in NOMID is not known. Objectives: To study the efficacy and safety of a long acting IL-1β inhibitor, canakinumab in NOMID. (ClinicalTrials.gov number, NCT00770601 ) Methods: 6 pts ages 11 to 34 with rash, systemic inflammation and CNS disease and typical arthrophathy (n=5) were enrolled in this 24-month, open label phase III study. Pts were previously treated with anakinra and underwent a one day withdrawal. The initial dose was 150 mg (or 2 mg/kg) or 300 mg (or 4 mg/kg in children) sc with repeat doses of 300 mg (or 4 mg/kg) sc every 4 to 8 weeks with dose escalation up to 600 mg (or 8 mg/kg) sc if evidence of disease activity persisted. Complete disease remission was defined based on patient-reported weekly clinical components (global diary score ≤2 and headache score <0.5) and measures of systemic inflammation (serum CRP ≤10 mg/L) and CNS inflammation (WBC count in CSF ≤15 cells/mm 3 ). Hearing, vision and safety were also assessed. Results: Although some pts flared after anakinra withdrawal, symptoms and serum inflammatory markers improved with canakinumab. At Month 6, 5/6 pts achieved remission based on diary scores, but no pt achieved complete remission due to CRP elevation (1/6) and persistent CNS leukocytosis (5/6). Two of the 6 pts had the lumbar puncture at 8 rather than 6 months. At the last available data point (range 195-750 days, median 550.5 days), 5/6 pts achieved remission based on diary scores and CRPs ≤10 mg/L, but 4/6 pts continued to have CNS leukocytosis. From time 0, visual acuity and visual field were stable in all 6 pts and a hearing loss from 15 to 30db in three consecutive frequencies (500 – 2000Hz) was observed in 1/10 ears that could reliably be tested. All pts required dose escalation to the maximum allowable dose of 600 mg (or 8 mg/kg) sc every 4-6 weeks. Adverse events (AEs) were mainly related to infections – during this study twelve infection-related AEs were reported by a total of 6 pts. One Serious AE (an abscess due to a methicillin-resistant Staphylococcus aureus infection) was considered to be study drug related. Conclusions: Canakinumab at the studied doses improves symptoms and serum inflammatory features of NOMID, although low grade CNS leukocytosis in four pts and headaches in one additional patient persisted. The question of whether further dose intensifications could be beneficial in these cases remains to be assessed. Canakinumab at doses up to 600 mg (or 8 mg/kg in children) sc every 4-6 weeks was overall well tolerated. Disclosure of Interest: R. Goldbach-Mansky Grant/Research support from: Regeneron, Novartis and Biovitrum, C. Sibley: None Declared, S. Felix Employee of: Novartis Pharma AG, C. Brewer: None Declared, K. King: None Declared, C. Zalewski: None Declared, H. Kim: None Declared, R. Bishop: None Declared, A. Chakraborty Employee of: Novartis Pharmaceuticals Corporation, L. Colin Employee of: Novartis Pharma AG, A. Chioato Employee of: Novartis Pharma AG